Hsa_circRNA_0059655 plays a role in salivary adenoid cystic carcinoma by functioning as a sponge of miR-338-3p - Zhao, Fei; Chen, Chu-Wen; Yang, Wen-Wen; Xu, Li-hua; Du, Zhi-hao; Ge, Xi-Yuan; Li, Sheng-Lin (Cellular and Molecular Biology, 2018)
Circular RNAs(circRNA) are recently demonstrated to have a close relationship with tumors.To investigate the role of circular RNA in the pathogenesis of salivary adenoid cystic carcinoma(SACC), ten SACC tissues and paired normal submandibular gland(SMG) tissues were collected as the tumor group and the control group. Total RNA was extracted and then measured using ceRNA microarray (including mRNA, lncRNA, and circRNA) and miRNA microarray. Gene Ontology(GO) analysis and Kyoto Encyclopedia of Gene and Genomes (KEGG) pathway analysis were performed in order to investigate the function of the differential expressing genes. The ceRNA regulatory network was constructed to find the core circRNAs. Then the role of circRNA on proliferation was examined in the SACC cell line SACC-83 using CCK-8,qRT-PCR and western blotting, and its roles on migration and invasion were examined using wound healing assay and transwell assay. The results of the microarrays showed that 3792 mRNAs, 7649 lncRNAs, 11553 circRNAs, and 132 miRNAs expressed differentially. The ceRNA regulatory network analysis showed that hsa_circ_0059655 and other 14circRNAs derived from PYGB target on several similar genes by miR-338-3p.Among the 15 circRNAs derived from PYGB, hsa_circ_0059655has the most relationships in the ceRNA network. Furthermore, after hsa_circ_0059655 was knocked down in SACC-83 cells, the expression of hsa-miR-338-3p was up-regulated while CCND1was down-regulated. The proliferation, migration, and invasion of SACC-83 cells also decreased after hsa_circ_0059655 knock-downed.Taken together, the circRNAs derived from PYGB may regulate the tumorigenesis and development of SACC through competing with miR-338-3p.